Patient perceptions of in‐hospital laboratory blood testing: A patient‐oriented and patient co‐designed qualitative study - Surakshya Pokharel; Zoha Khawaja; Jonathan Williams; Adnan Adil Mithwani; Kimberly Strain; Prachi Khanna; Anna Rychtera; Veronika Kiryanova; Karen Tang; Pamela Mathura; Chris Hylton; Anshula Ambasta (Wiley, 2024)
Abstract Background Indiscriminate use of laboratory blood testing in hospitals contributes to patient discomfort and healthcare waste. Patient engagement in low‐value healthcare can help reduce overuse. Understanding patient experience is necessary to identify opportunities to improve patient engagement with in‐hospital laboratory testing. Objectives To understand patient experience with the process of in‐hospital laboratory blood testing. Methods We used a qualitative study design via semistructured interviews conducted online or over the phone. Participants were adult patients or family members/caregivers (≥18 years of age) with a recent (within 12 months of interview) experience of hospitalization in Alberta or British Columbia, Canada. We identified participants through convenience sampling and conducted interviews between May 2021 and June 2022. We analysed transcripts using thematic content analysis. Recruitment was continued until code saturation was reached. Results We interviewed 16 participants (13 patients, 1 family member and 2 caregivers). We identified four themes from patients' experiences of in‐hospital laboratory blood testing: (i) patients need information from healthcare teams about expected blood testing processes, (ii) blood draw processes should consider patient comfort and preferences, (iii) patients want information from their healthcare teams about the rationale and frequency of blood testing and (iv) patients need information on how their testing results affect their medical care. Conclusion Current laboratory testing processes in hospitals do not facilitate shared decision‐making and patient engagement. Patient engagement with laboratory testing in hospitals requires an empathetic healthcare team that provides clear communication regarding testing procedures, rationale and results, while considering patient preferences and offering opportunities for involvement. Patient or Public Contribution We interviewed 16 patients and/or family members/caregivers regarding their in‐hospital laboratory blood testing experiences. Our findings show correlations between patient needs and patient recommendations to make testing processes more patient‐centred. To bring a lived‐experience lens to this study, we formed a Patient Advisory Council with 9-11 patient research partners. Our patient research partners informed the research design, co‐developed participant recruitment strategies, co‐conducted data collection and informed the data analysis. Some of our patient research partners are co‐authors of this manuscript.